The Implementation of Activity Based Learning (ABL) Method at Elementary School to Enhance Students' Speaking Skills - german, emilius (Universitas Pendidikan Ganesha, 2020)
Learning a foreign language can effectively take place in childhood, which is usually called the golden period. However, recent data shows the number of problems faced by elementary school students. One of the main problems identified is oral competency. This is due to a lack of teachers’ knowledge of teaching methods. The primary objective of this study is to identify whether the implementation of an activity- based learning (ABL) method can improve students’ speaking skills at the Elementary School level. Classroom action research with two cycles was used to investigate the impact of the method at Permata Bangsa Elementary school. The data was collected through observation on 17 students while doing activities and tests administered at the end of each cycle to obtain the result of the learning process. The data obtained were then compared, and the results show the influence on students’ improvement in speaking. Thus, the implementation of ABL at the elementary school can significantly enhance students’ oral competency.